Get to Know the Strategic Role of Cooperatives and SMes in the Indonesian Economy - Hana Yatira; Armaida Raptama Sagala; Arini Rosalina; Khashia Daffa Aulya; Putri Realita F (PT FORMOSA CENDEKIA GLOBAL, 2024)
Cooperatives and Small and Medium Enterprises (UKM) play a crucial role in Indonesia's economic development in accordance with the spirit stated in Article 33 of the 1945 Constitution. This research aims to explore the role of cooperatives and SMEs in the context of the intent of Article 33, as well as analyzing the differences between cooperatives and SMEs in economic empowerment. Through a literature approach, this research identifies the contribution of cooperatives and SMEs in creating jobs, reducing economic disparities and strengthening the local economy. Analysis of the intent of Article 33 of the 1945 Constitution highlights the state's commitment to encouraging sustainable and inclusive economic development, which is based on the principle of kinship. However, challenges such as limited access to capital and technology and lack of supporting infrastructure still hinder the implementation of the intent of Article 33. Therefore, collaboration between the government, cooperatives, SMEs and the private sector is needed to create a conducive environment for the growth of cooperatives and SMEs in Indonesia